(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the study of the theoretical foundations of the use of the polygraph in forensics. The role of the polygraph as a tool for obtaining indicative information during the investigation of crimes is considered. The legal aspects of the use of the polygraph are analyzed, in particular, its place in the system of evidence and observance of human rights. The principles of the polygraph are described in detail, including the physiological reactions that are registered and the methods of their interpretation. The article considers the issues of ethics and reliability of the results of polygraph studies.